High efficiency synthesis of HKUST-1 under mild conditions with high BET surface area and CO2 uptake capacity - Chen, Yipei; Mu, Xueliang; Lester, Edward; Wu, Tao (Elsevier, 2018)
This study focuses on the development of a hydrothermal method for the rapid synthesis of good quality copper benzene-1,3,5-tricarboxylate (referred to as HKUST-1) with high yield under mild preparation conditions to address the issues associated with reported methods. Different synthesis conditions and activation methods were studied to understand their influence on the properties of HKUST-1. It was found that mixing the precursors at 50 °C for 3 h followed by activation via methanol refluxing led to the formation of a product with the highest BET specific surface area of 1615 m2/g and a high yield of 84.1%. The XRD and SEM data illustrated that the product was highly crystalline. The sample was also tested on its capacity in CO2 adsorption. The results showed strong correlation between surface area of the sample and its CO2 uptake at 1 bar and 27 °C. The HKUST-1 prepared in this study demonstrated a high CO2 uptake capacity of 4.2 mmol/g. It is therefore concluded that this novel and efficient method can be used in the rapid preparation of HKUST-1 with high surface area and CO2 uptake capacity.